2018
DOI: 10.1139/apnm-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Using velocity loss for monitoring resistance training effort in a real-world setting

Abstract: The purpose of the present study was to evaluate the changes in movement velocity during resistance training with different loads while the trainees attempted to move the load at a predetermined repetition duration. Twenty-one resistance-trained men (age: 25.7 ± 5 years; height: 177.0 ± 7.2 cm; mass: 85.4 ± 13.56 kg) volunteered to participate in the study. Participants performed 2 test sessions. The first to determine 1-repetition maximum (1RM) load, and the second to evaluate velocity loss during a set to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Our findings are in agreement with previous studies that reported high levels of muscle activation during no load resistance training [ 21 , 27 ] for the arm muscles in many different situations. Counts et al [ 20 ] reported high levels of biceps brachii muscle activation during NL-VF in untrained men and women.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings are in agreement with previous studies that reported high levels of muscle activation during no load resistance training [ 21 , 27 ] for the arm muscles in many different situations. Counts et al [ 20 ] reported high levels of biceps brachii muscle activation during NL-VF in untrained men and women.…”
Section: Discussionsupporting
confidence: 94%
“…This study also analyzed both peak and mean EMG activity; however, it did not compare muscle activation between TRT and no load resistance training. Considering that both studies [ 21 , 27 ] involved upper limb exercises, the present results extend the observation to lower body muscles and brings information for the possible use of no load resistance training to other body parts.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The VBT has important practical implications for the design and implementation of individual training plans. On one hand, coaches are provided with quantitative outcomes that can be used for multiple purposes, such as training autoregulation through the warm-up loads' velocity assessment [2,4,5], determination of individualised load-velocity profiles [6] and the real-time neuromuscular fatigue monitoring [4,7]. On the other hand, practitioners receive instantaneous performance feedback about the actual velocity developed during each lift, which has been shown to produce greater adaptation and larger training effects [8].…”
Section: Introductionmentioning
confidence: 99%